What Do Artists Know? - Elkins, James, 1955- (Book collections on Project MUSE., 2012)
"Brings together historians, philosophers, critics, curators, artists, and educators to ask how art is and should be taught. Explores the theories that underwrite art education at all levels, the pertinent history of art education, and the most promising current conceptualizations"--Provided by publisher